Intracellular calcium imaging for agonist screening - Wang, Haojie; Yang, Bo; Mo, Liangzhu; Yang, Hua-Qian (Biophysics reports, 2025)
Calcium ions are involved in the regulation of a wide range of physiological activities such as nerve conduction, muscle contraction, cell division and gene expression through local calcium transients and global calcium oscillations. Calcium homeostasis modulator 1 (CALHM1) is a novel plasma membrane large-pore ion channel mediating calcium influx. Therefore, screening for novel CALHM1 agonists or antagonists is very important for the research of physiological and pathological processes and the development of therapeutic drugs for related diseases. In this protocol, we presented the detection of real-time calcium dynamics in transiently transfected cell lines and primary cells with genetically encoded calcium indicators or calcium indicator dyes, respectively. A comprehensive step-by-step approach has been outlined for drug screening and validation to offer a valuable guide for utilizing calcium imaging to investigate calcium-related physiological processes.